ANALISIS YURIDIS PELAKSANAAN SUMPAH JABATAN DAN KODE ETIK NOTARIS/PPAT YANG BERKEDUDUKAN SEBAGAI KREDITUR DALAM SENGKETA KEPAILITAN ( STUDI KASUS PUTUSAN PENGADILAN NIAGA NO. 02/PAILIT/2011/PN.NIAGA.SMG ) - , SANG HAPSARI ARUM KUSUMA PUTRI, Dr.Paripurna P.Sugarda,S.H.,M.Hum.,LL.M ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The thesis is aimed for ackwnoledge the essence and the bounding of Oath of Office and Code of Ethic of Notary/PPAT as well as Creditor of PT. Sarwo Indah and comprehend the possibility of violance of Oath of Office and Code of Ehic of Notary/PPAT conducting house rading process as known as creditor in PT. Sarwo Indah. Thus, the research is used two combined research methods, Empirical and Juridical, therefore, the methodology approach is empirically juridical. The juridical research is done by observing lierature materials, called secondar data, that is known as legal research of literature. While, the empirical research is conducted by collecting and gathering primary data obtained from research location that becomes the subject of research. A qualitative analysis is implemented, either on primary or secondary data that are arranged systematically. Thus, the conclusion of each problem formulation is done by inductive method. Hence, the research finding shows that there is a essence and bounding of Oath of Office and Code Ethic of Notary/PPAT as well as Creditor in PT. Sarwo Indah. The Oath of Office and Code of Ethic of Notary/PPAT are meant by Spirit of the position implementation shown by responsbility, independent, honest and non-profit oriented and rationality. Thus, the bounding, itself, means merely concerning on moral sanction where is highly weak caused by the less coordination and communicaion of inter-institution and organization related the oath of office and code of ethic enforcement. There is a violance of Oath of Office and Code of Ethic of Notary/PPAT because here is a weakness of legal interpretation, personal value and personality regarding motivation, herefore, it affects on the final goal of the position implementation of Notary/PPAT.